Increasing interest of students from under‐represented groups in medicine—A systematised review. (27th May 2020) - Reeves, Nicole S.; Cheek, Colleen; Hays, Richard; Sargent, Aryelle; McComiskie, Alice; Santini, Carlos; Nguyen, Jamie; Chalwe, Khezia; Mubarak, Adil
Abstract: Objective: Community engagement activities are the entry point to a "pipeline" of activity aimed at supporting under‐represented students and nurturing their interest in medical careers following graduation. This review aimed to describe the range of activities medical schools undertake to encourage and support rural students or other targeted under‐represented populations to apply to medical school, and the reported outcomes. The overarching aim was to identify which programs prior to application into medicine are most effective. Design: A systematised review. Setting: Medical Education articles published January 2000 to May 2018. Participants: Population groups under‐represented in medicine, including rural students. Interventions: Programs delivered to participants prior to application to medical school. Main outcome measures: Reach, format and duration of programs, number of participants applying and completing medical school. Results: A search of several databases identified 2688 articles. After filtering for relevance, 1271 articles were considered for the final review. Of the 155 full‐text articles assessed, 133 were excluded as they did not meet the eligibility criteria. A further three articles were added on review of references. Nine reviewers conducted data abstraction from 25 articles. Conclusion: There is a need for improved evidence to define the best ways to support under‐represented groups in medicine. Important features appear to be targeting interested students and supporting their attainment of entry requirements. Successful programs might be those which enhance a student intake representative of the population.